Behavior at work: propositions for optimizing the human and organizational challenges of digital materials passports - Vladislav Hristov Grozev; Carolyn Axtell; Hui Zhang; Karina Nielsen (Frontiers in Manufacturing Technology)
There is growing research on the implementation of Digital Materials Passports (DMPs) in different industries, yet there is lack of guidance for preparing the human and organizational components within this ecosystem of change. To help fill this void, in this position paper, we develop propositions for dealing with the people and organizational challenges of implementing DMP’s within organizations and across supply chains. Applying a socio-technical systems approach, we highlight the interconnectedness between the human, organizational, and technical factors when designing and implementing DMPs. We also use the IGLOO framework which highlights that organizational support needs to occur at the individual, group, leader, organizational, and omnibus (interorganizational) levels. We draw on research from the literature on human behavior at work, covering areas such as social identity, trust, resilience in organizations, leadership, participatory job redesign, and training and learning as mechanisms to reduce socio-technical challenges and to reach important interorganizational goals. Understanding these mechanisms helps us to develop seven propositions that organizations and supply chains can put in place when implementing DMPs. These propositions can offer mutually reinforcing support for organizations when implemented, and can be adapted to consider both the long-term and the immediate implementation context. We also discuss the role of employee involvement in enhancing the benefit of the propositions for organizations and supply chains in moving towards Industry 5.0.